2020
DOI: 10.1007/s11024-020-09419-0
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometrics in Academic Recruitment: A Screening Tool Rather than a Game Changer

Abstract: This paper investigates the use of metrics to recruit professors for academic positions. We analyzed confidential reports with candidate evaluations in economics, sociology, physics, and informatics at the University of Oslo between 2000 and 2017. These unique data enabled us to explore how metrics were applied in these evaluations in relation to other assessment criteria. Despite being important evaluation criteria, metrics were seldom the most salient criteria in candidate evaluations. Moreover, metrics were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 54 publications
1
16
0
1
Order By: Relevance
“…The second suggested that increasing internationalization of disciplines would lead to isomorphism and a prominence of field-dependent preferences (Lamont 2009). In line with the second expectation and based on prior studies, we expected that economists would more strongly value candidates' bibliometrics (Hylmö 2018), while physicists would place more value on their research profiles due to a larger degree of functional dependency among researchers (Reymert 2020;Whitley 2000). In line with our first expectation, we expected researchers in the Netherlands to be least concerned with bibliometrics because their funding model does not include bibliometric indicators (Aagaard 2015;Sivertsen 2017).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The second suggested that increasing internationalization of disciplines would lead to isomorphism and a prominence of field-dependent preferences (Lamont 2009). In line with the second expectation and based on prior studies, we expected that economists would more strongly value candidates' bibliometrics (Hylmö 2018), while physicists would place more value on their research profiles due to a larger degree of functional dependency among researchers (Reymert 2020;Whitley 2000). In line with our first expectation, we expected researchers in the Netherlands to be least concerned with bibliometrics because their funding model does not include bibliometric indicators (Aagaard 2015;Sivertsen 2017).…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, we assume that both fields apply different evaluative criteria where researchers in economics should place stronger emphasis on the importance of metrics, while researchers in physics, to a larger extent, emphasize candidates' research profiles in order to assess how they might fit into a research group. This difference between the two fields has also been documented by recent qualitative studies building on confidential recruitment reports (Reymert 2020). Finally, both fields are characterized by a high degree of internationalization.…”
Section: Empirical Context: Fields and Countriesmentioning
confidence: 68%
See 1 more Smart Citation
“…Samtidig tillegges publisering betydning også i andre sammenhenger innenfor akademia. Tall over vitenskapelig publisering -såkalte bibliometriske indikatorer -brukes i finansierings-og evalueringssammenheng (Wilsdon mfl., 2015), og antall publikasjoner har betydning for ansettelser og stillingsopprykk (Reymert, 2020). Internt i forskersamfunnet ser en også at mange markedsfører sine prestasjoner gjennom å vise til publiseringsmål som h-indeks eller RG-skår på Researchgate -en type «Facebook» for forskere.…”
Section: Innledningunclassified
“…According to Campbell et al (2010), there seems to be a consensus among researchers that the study of publications and citations, bibliometry, is an "objective, reliable, and cost-effective measure of peer-reviewed research outputs" (Campbell et al, 2010, p. 66). Various indicators of scientific productivity are used as a basis for employment, promotion, and allocation of research funding (Reymert, 2020;Wilsdon et al, 2015). In addition, bibliometry is considered a reliable tool for assessing and managing R&D funding (European Science Foundation, 2009).…”
Section: Introductionmentioning
confidence: 99%